15.IDENTIFICATION OF COMMON AEROBIC BACTERIAL ISOLATES AMONG CONJUNCTIVITIS IN SULAYMANIYAH PROVINCE / IRAQ (Iraqi Journal of Medical Sciences, 2018)
Background: Bacterial conjunctivitis is a microbial infection of the mucous membrane of the conjunctiva of eye that occurs both in adults and children. It is produced by an array of microorganisms that is frequently isolated from the conjunctiva of healthy subjects. The normal conjunctival flora represents both bacterial colonization and transient or recurring bacterial contamination. Coagulase-negative Staphylococci and Corynebacteria are frequently present on the healthy conjunctiva, but more traditionally pathogenic organisms, such as coagulase-positive Staphylococci, Streptococci, Haemophilus species, Moraxellae and Gram negative coliform rods occasionally isolated from normal, non-inflamed eyes.Objective: To determine etiological agents of aerobic bacterial conjunctivitis and the prevalence of each bacteria and its relation with the conjunctival discharge.Methods: This study conducted on 100 conjunctival samples from patients with conjunctivitis, and 50 samples from healthy normal persons. All samples were cultured on enriched media like blood agar and chocolate agar, anti-microbial susceptibility of all 100 samples from patients were analyzed.Results: The prevalence of aerobic bacterial conjunctivitis is 53 %with predominance age of 1-10 years. The most common bacterial isolates were Staphylococcus epidermidis followed by Streptococcus pneumonia. Most of the isolates were sensitive to cefotaxime and ofloxacillin, while different result was detected regarding resistance of each isolated bacteria.Conclusion: Aerobic bacterial isolates can be detected both in conjunctivitis and normal healthy individual with similarity regarding the type of bacteria that affect all age group.Keywords: Conjunctivitis, commensal flora, conjunctival dischargeCitation: Anoar KA, HassanTM, Majid BT. Identification of common aerobic bacterial isolates among conjunctivitis in Sulaymaniyah Province / Iraq. Iraqi JMS. 2018; 16(2): 223-229. doi: 10.22578/IJMS.16.2.15
Keywords: Conjunctivitis; commensal flora; conjunctival discharge